Quelato complexos de oxovanádio (IV): potenciais mimetizadores de insulina - Barbosa, Andrey Castro (2004)
Based on studies of another studies that explored the capacity of oxovanadium(IV) ion to mimic insulin, we had the idea to contribute with this line of research. For this, our choice of ligands was trans - 1,2 diamineciclohexane - N,N,N`,N` - tetraacétic (CDTA) and ethilenediaminetetraacétic (EDTA) acids, to synthesize the [VO(CDTA)], Na2[VO(EDTA)] and [(VO)2(EDTA)].4H2O complexes. These compounds were characterized by Infrared Spectroscopy, Ultraviolet and Visible Spectroscopy, Cyclic Voltammetry and Elemental Analysis. We also used Electronic Paramagnetic Resonance for compounds that contain EDTA ligands and X Ray analysis to analyze the compounds that contains two metallic centers. The last compound was used in biologic tests in Wistar rats.